2005
DOI: 10.1111/j.1477-9552.2005.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐varying Hedge Ratios: A Principal‐agent Approach

Abstract: We use the classic agency model to derive a time-varying optimal hedge ratio for low-frequency time-series data: the type of data used by crop farmers when deciding about production and about their hedging strategy. Rooted in the classic agency framework, the proposed hedge ratio reflects the context of both the crop farmer's decision and the crop farmer's contractual relationships in the marketing channel. An empirical illustration of the Dutch ware potato sector and its futures market in Amsterdam over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, we are careful to generalize these results to other markets because of certain distinct characteristics of those markets. Food markets may share some similar characteristics but not all markets are totally the same because of the differences in the bargaining power of actors, market risk, coordination costs, competition and characteristics of the products in these markets (Kuwornu, Kuiper and Pennings, 2004; Kuwornu et al , 2005; Kuwornu, 2006; Kuwornu and Saqib, 2017). Therefore, we may be over generalizing if we extend the results to other markets around the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we are careful to generalize these results to other markets because of certain distinct characteristics of those markets. Food markets may share some similar characteristics but not all markets are totally the same because of the differences in the bargaining power of actors, market risk, coordination costs, competition and characteristics of the products in these markets (Kuwornu, Kuiper and Pennings, 2004; Kuwornu et al , 2005; Kuwornu, 2006; Kuwornu and Saqib, 2017). Therefore, we may be over generalizing if we extend the results to other markets around the world.…”
Section: Discussionmentioning
confidence: 99%
“…produce, process and sell) as individuals, since these farmers possess low or no bargaining power and lack the necessary information regarding developments in the market, especially in emerging economies. In this respect, farmers are exploited by marketing firms such by middlemen, wholesalers, processors, exporters and retailers (Kuwornu, Kuiper and Pennings, 2004; Kuwornu, Kuiper, Pennings and Meulenberg, 2004). Numerous studies have revealed that cooperative organization and networks yield enormous benefits to farmers and cooperatives (e.g.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The WRS is one of the market risk management instruments to reduce unstable prices, and it is consistent with long-term market development [66]. Futures contracts are another price risk management instrument for actors in food marketing channels [67][68][69][70][71][72].…”
Section: Farmers' Perceptions Of the Warehouse Receipt Systemmentioning
confidence: 99%
“…Lee and Yoder [3] developed a new bivariate Markov Regime Switching BEKKGeneralized Autoregressive Conditional Heteroscedasticity (GARCH) model to estimate. Kuwornu et al [4] used the classic agency model to derive a time-varying optimal hedge ratio for low-frequency time-series data. Huang et al [5] derive a new mean-risk hedge ratio based on the concept of Value at Risk (VaR).…”
Section: Introductionmentioning
confidence: 99%